OP0313 THERAPEUTIC APPROACHES TO OSTEOSARCOPENIA: DENOSUMAB EFFECT ON FALLS RISK, PHYSICAL PERFORMANCE AND WALKING SPEED. (2nd June 2020) - El Miedany, Y.; El Gaafary, M.; Toth, M.; Hegazi, M. O.; El Aroussy, N.; Hassan, W.; Almedany, S.; Nasr, A.; Bahlas, S.
Abstract : Background: There is a strong association between osteoporosis and skeletal muscle dysfunction. Heparan-sulfate proteoglycans are abundant in skeletal muscles and may represent a target for RANKL inhibitor. It was noted that patients who completed their planned denosumab therapy course (5-years) started to sustain falls. Objectives: To assess the effect of Denosumab on falls risk, physical performance, grip strength and gait speed and whether there is a relation with bone mineral density. Methods: 127 osteoporotic patients treated with denosumab were assessed prior to starting denosumab therapy for: baseline BMD using DXA scan, blood test for osteoporosis bone profile, self-reported falls risk using (FRAS score [1]), fracture risk using FRAX, handgrip strength using a calibrated dynamometer (the best of three trials of the dynamometer testing was recorded), the patient's physical performance assessed by testing for: Short Physical Performance Battery (SPPB), Timed Up and Go (TUG), and the 4 Meter Walk Gait Speed. Same measures were assessed again after completing 5-years of denosumab therapy. Comparison groups included 112 patients diagnosed to have osteoporosis and treated with zoledronate (Zol), once yearly IV injection, for 3-years; and 134 patients treated with once weekly oral alendronate (Aln) 70mg for 5-years. The patients were assessed for the same parameters as in the denosumab therapy. All the measures were reassessed 1-year after stopping the osteoporosis therapy. Results: No differences were seen on comparing the baseline parameters of the 3 groups. In comparison to the baseline, there was significant increase in the BMD in the 3 groups, Denosumab /Zol/Aln at both spine and hip (P = 0.02) at 5-, 3- and 5-years of treatment respectively. In the denosumab group, at 5-years of therapy, there was significant decrease in falls risk score (-1.4, 95% CI = −2.8 to −0.7; P = .01), significant improvements in the grip strength (+4.2Kg, P = 0.01), SPPB score (1.2 points; 95% CI = −0.07 to 2.2; P = .02), TUG (1.7 seconds; 95% CI = −2.2 to 0.1; P = .031) and gait speed (0.1 m/s; 95% CI = 0.03-0.2; P = .01). Zol and Aln improved significantly SPPB score (0.9 and 0.8 points; P = .04), TUG (1.4 and 1.3 seconds; P = .05) and gait speed (0.2 and 0.3 m/s; P = .02) respectively, however, there was no significant change in the falls risk (p = 0.06 and 0.07 respectively). 1-year after stopping Denosumab, there was significant worsening of the falls risk score, grip strength, SPPB score, TUG and gait speed (P = 0.1). There was no difference in all the measures 1-year after stopping Zol and Aln. There was no relation to the increase in BMD gained. Conclusion: Denosumab displayed positive impact and significant improvements in physical performance, grip strength and gait speed. Also, Denosumab, enhanced multidirectional agility as depicted by TUG. Collectively, this would explain the reduction of falls risk which got worse on stopping the medication. Osteoporosis and sarcopenia share similar risk factors, highlighting muscle-bone interactions, which may result in debilitating consequences, such as falls and fractures. RANK/RANKL/OPG pathway, a key regulator of bone homeostasis, may contribute also to the regulation of skeletal muscle integrity and function. References: [1]El Miedany et al. Falls Risk Assessment Score (FRAS). J Clin Gerontology and Geriatrics 2011; 21-26. Acknowledgments: Ali El Miedany for his help in data entry Disclosure of Interests: None declared